Mortality of Diatraea saccharalis is affected by the pH values of the spore suspension of Beauveria bassiana and Metarhizium anisopliae - de Souza, Tamires Doroteo [UNESP]; Sanches, Ariadne Costa [UNESP]; Cruz, Maiara Alexandre [UNESP]; do Prado, Thais Juliane [UNESP]; Savi, Patrice Jacob [UNESP]; Polanczyk, Ricardo Antônio [UNESP] (FapUNIFESP (SciELO), 2022)
Fungal virulence is multifaceted and dependent on multiple factors including the pH of the spore suspension. In this study, we accessed effects of six pH values of Beauveria bassiana, and Metarhizium anisopliae medium for the growth, sporulation, and mortality on sugarcane stalk borer Diatraea saccharalis. The culture of fungi was performed onplates containing the PDA (Potato Dextrose Agar) medium. Virulence was tested in D. saccharalis larvae distributed in four replicates of 15 larvae. To evaluate the performance of the isolates, they were grown at different pH values in an artificial chitin medium to confirm the degradation capacity of the fungi at each pH. No significant difference was observed for the sporulation at pH ranged from 4 to 9 for both fungi. In the mortality assay, larval mortality was higher at pH 7 and 8 for both fungi, reaching 87% for B. bassiana and 81% for M. anisopliae.
Keywords: Entomopathogenic fungi; Microbial control; Sugarcane borer